Auditor Choice in Indonesia Listed Family Firms - Hasni Yusrianti; Tertiarto Wahyudi; Aryanto Aryanto (Faculty of Economics, Universitas Sriwijaya, 2023)
This study aims to empirically examine the auditor choice in family firms. The study investigates the relationship between family firms, family ownership, and the family identity of the CEO with auditor choice. The research sample consists of 931 firm-year observations non-financial listed companies on the Indonesia Stock Exchange in 2015- 2021. A company is considered to use a high-quality auditor if it is audited by one of the BIG 4 Firms. Logistic regression analysis results indicate that family firms are less likely to hire high-quality auditors compared to non-family firms. Besides, the percentage of family ownership is negatively related to auditor choice, where companies with higher family ownership less likely to hire high-quality auditors. In terms of the family identity of the CEO, companies with a descendant CEO are less likely to hire high-quality auditors. However, the presence of a founding family CEO and a professional CEO is not related to auditor choice.